Industrial training report: Raudhah Management & Services / Wan Hazrina Wan Zahari - Wan Zahari, Wan Hazrina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about experience gained during the industrial training period at Raudhah Management & Services, which was started by Nor Jamilah Binti Muhamad in June 2023. During the training, many important skills were learned such as organized documents and handling clients. Much information has been told in this report, especially about the company secretary’s job. This report also comments on industrial training program that will be undertaken by every student. It is explaining what to expect and the skills that will be learned during the training.